2012
DOI: 10.1007/s00264-012-1594-6
|View full text |Cite
|
Sign up to set email alerts
|

Muscular atrophy of the lower leg in unilateral post traumatic osteoarthritis of the ankle joint

Abstract: Purpose Muscle atrophy is a commonly encountered problem in osteoarthritis (OA). The aim of this study was to estimate the amount of muscle atrophy and fatty degeneration of the lower leg muscles related to ankle OA by magnetic resonance imaging (MRI). Methods Twenty-one patients with unilateral ankle OA were included in this cohort study. Calf circumference of the affected and healthy lower leg was documented. The degree of OA was classified in conventional radiographs. The cross-sectional areas and fatty deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…The binary masks were subsequently applied on maps of T2, MD, FA, RD, and fat fraction to generate the average value. Muscle volumes of soleus were also quantified as the cross‐sectional area on the central slice of the T1‐weighted anatomic image . Eighteen subjects per group sufficiently afforded >80% power to detect an effect size of 0.85, with a measurement error of 30% at an alpha of 0.05 (as measured by PCr recovery halftime).…”
Section: Methodsmentioning
confidence: 99%
“…The binary masks were subsequently applied on maps of T2, MD, FA, RD, and fat fraction to generate the average value. Muscle volumes of soleus were also quantified as the cross‐sectional area on the central slice of the T1‐weighted anatomic image . Eighteen subjects per group sufficiently afforded >80% power to detect an effect size of 0.85, with a measurement error of 30% at an alpha of 0.05 (as measured by PCr recovery halftime).…”
Section: Methodsmentioning
confidence: 99%
“…for review). Given that intramuscular adipose has been shown to increase and muscle mass has been shown to decrease in individuals with OA, longitudinal research is needed to quantify the extent to which these parameters change before versus after surgery. The fact that the current study demonstrated that no changes occur in the relative size of the muscle compartments between the fused and control limbs supports the theory that changes in tissue composition may occur pre‐operatively.…”
Section: Discussionmentioning
confidence: 99%
“…The paucity of data examining muscle function following tibiotalar arthrodesis limits our understanding of the relationship between tibiotalar joint motion, ankle strength, and post‐operative impairments. For example, end‐stage ankle OA is known to cause muscle atrophy, and studies postulate that this atrophy occurs because individuals limit their activities to avoid pain . If true, atrophy should reverse post‐operatively due to the elimination of pain.…”
mentioning
confidence: 99%
“…Furthermore, the major postural muscles of the lower limbs including quadriceps, gluteus, and hamstrings are affected (wasting and or compensatory over activity) with arthrosis of knee and hip joints [25][26][27] , affecting the balance and increasing the risk of fall. Muscles affected significantly in end stage ankle arthrosis include medial soleus and only fatty degeneration was reported in other muscles [28] . This may be the reason postural stability remains preserved in ankle arthrosis as well as why gait variability parameters are not as important in ankle arthrosis as they are in arthrosis of other weight bearing joints.…”
Section: Discmentioning
confidence: 99%